2021
DOI: 10.3390/ma14040743
|View full text |Cite
|
Sign up to set email alerts
|

Resins for Frontal Photopolymerization: Combining Depth-Cure and Tunable Mechanical Properties

Abstract: Photopolymerization has undergone significant development in recent years. It enables fast and easy processing of materials with customized properties and allows precise printing of complex surface geometries. Nevertheless, photopolymerization is mainly applied to cure thin films since the low curing depth limits the fast production of large volumes. Frontal photopolymerization (FPP) is suitable to overcome these limitations so that curing of centimeter-thick (meth)acrylic layers can be accomplished within min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The current study showed that composites with an added color modifier of greater than 1 wt% exhibited DC values lower than 40%, even after being light-cured for 40 s. It is known that the maximum curing depth in light-activated free-radical polymerization is limited by the attenuation of curing light. This could be explained using Beer-Lambert's law [33,34] (Equation ( 6))…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that composites with an added color modifier of greater than 1 wt% exhibited DC values lower than 40%, even after being light-cured for 40 s. It is known that the maximum curing depth in light-activated free-radical polymerization is limited by the attenuation of curing light. This could be explained using Beer-Lambert's law [33,34] (Equation ( 6))…”
Section: Discussionmentioning
confidence: 99%
“…[40,41] The cationic frontal photopolymerization, known as radical-induced cationic frontal polymerization (RICFP) technique, is very promising for curing thick epoxy samples, as already reported in the literature. [42][43][44] The mechanism involves the photo-cleavage of an iodonium salt which generates a superacid that can start the cationic ring-opening epoxy polymerization. The heat release will cleave the thermo-labile initiator generating reactive radicals, which are oxidized in the presence of iodonium salt, forming a reactive carbocation.…”
Section: Introductionmentioning
confidence: 99%
“…Photobleaching PIs undergo photochemical reactions under irradiation, causing the absorbance in the visible-light region to decrease or even disappear completely; this effect can not only realize the colorlessness of materials but also increases light penetration to obtain thick materials. 41,42 Therefore, the development of visible LED PIs with photobleaching properties is of great importance for photocuring. Considerable work has been done on photobleaching PIs, including type I PIs, such as tetrakis (2,4,6-trimethylbenzoyl) stannane 43 and coumarin oxime esters, 44,45 and type II PIs, such as cinna-moyl, 46 curcumin, 47 and thiacarbocyanines.…”
Section: Introductionmentioning
confidence: 99%